HOW CORPORATE SOCIAL RESPONSIBILITY EFFECTS COMPANY’S FINANCIAL PERFORMANCES - Nindya Farah Dwi Puspitasari; Nindhita Nisrina Sari (Sekolah Menengah Kejuruan (SMK) Pustek, 2021)
A successful business must pay attention not only to how to improve the welfare of shareholders, but also the welfare of all stakeholders. This study aims to see the effect of disclosure of Corporate Social Responsibility (CSR) on corporate financial performance. Financial performance is measured using three indicators, which are return on Equity (ROE), total stock return and Tobin’s Q. ROE represents company’s profitability, total stock return reflects company’s performance in the market and tobin’s Q shows firm value. CSR is measured using the Corporate Social Disclosure Index (CSRDI) which is based on the ISO 26000 standard. By using two controlling variables, company size and leverage, the results show that there is a negative and insignificant effect between CSR and ROE ratio. Although CSR practice together with control variables also has no effect on total stock returns, but there is a significant positive effect between CSR disclosures and firm value. These results can motivate company’s managers to include CSR as a management strategy to increase firm value by paying serious attention to stakeholders and sustainability issues.